KEBIJAKAN HUKUM PENANGGULANGAN TINDAK PIDANA MENGGUNAKAN GELAR AKADEMIK PALSU - Muhammad Ridwan Lubis (Lembaga Penelitian dan Pengabdian Pada Masyarakat (LPPM) Universitas Darma Agung (UDA) Medan, 2021)
Abstract This study aims to find out about the regulations regarding title counterfeiting based on the perspective of the Criminal Code. To achieve this goal, a normative juridical law research was conducted. Normative juridical legal research, namely legal research conducted by examining secondary data or library materials as the basic material to be researched by conducting searches on regulations and literature related to the problems studied. Based on the results of research and data analysis that has been carried out, it is concluded that the regulation regarding the crime of counterfeiting degrees in Indonesia is regulated in several statutory provisions, namely Article 263 of the Criminal Code.